2020
DOI: 10.3311/ppch.14959
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of N,N'-Diphenylguanidine in Non-Aqueous Aprotic Solvents and Alcohols

Abstract: Electrooxidation of N,N’-diphenylguanidine (1,3-diphenylguanidine) was investigated in aprotic (acetonitrile, acetone, dimethyl sulfoxide, dimethyl formamide, propyleneoxide, nitromethane) and alcoholic (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, benzyl alcohol) non-aqueous solvents at platinum electrode with cyclic voltammetry. Its concentration was 5 mM in most cases. In acetonitrile and acetone a sharp voltammetric peak appeared around 1 V vs. reference and currents measured in the subsequent sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is mainly true for polyaniline which has diverse applications [30]. On the other hand, in our earlier works [31,32] we demonstrated that organic compounds bearing amino groups can be easily oxidized electrochemically. Preliminary voltammetric studies of the sulphonate ions show that none of them has redox activity between 0 and 1 V except for sulphanilic acid (Fig.…”
Section: Results and Discussion 31 Cyclic Voltammetric Studies In Thmentioning
confidence: 90%
“…It is mainly true for polyaniline which has diverse applications [30]. On the other hand, in our earlier works [31,32] we demonstrated that organic compounds bearing amino groups can be easily oxidized electrochemically. Preliminary voltammetric studies of the sulphonate ions show that none of them has redox activity between 0 and 1 V except for sulphanilic acid (Fig.…”
Section: Results and Discussion 31 Cyclic Voltammetric Studies In Thmentioning
confidence: 90%
“…Electrochromic materials produced by electrochemical synthesis are generally based on monomeric electroactive compounds such as thiophene, carbazole, aniline, EDOT, pyrrole and their derivatives. Among these compounds, carbazole is preferred as the starting compound in scientific studies because of its suitable structure for electrochemical synthesis [2][3][4]. Below, the advantages offered by the carbazole unit used in these studies are briefly mentioned:…”
Section: Introductionmentioning
confidence: 99%